GAMBARAN EFIKASI DIRI SISWA KELAS XII AKUNTANSI DAN KEUANGAN LEMBAGA (AKL) DALAM MENGHADAPI UJI KOMPETENSI KEAHLIAN (UKK) DI SMK MAHARDIKA BATUJAJAR PADA MASA PANDEMI COVID-19 - Sulistia Fuji Awaliyah (IKIP Siliwangi, 2022)
This study aims to determine the description of self-efficacy at SMK Mahardika Batujajar class XII Accounting and Financial Institutions (AKL) during the covid-19 pandemic. This study uses a qualitative approach with a type of descriptive methodology. Data collection techniques used in the study were observation, interviews, and documentation. The data sources in this study were 2 Class XII students majoring in AKL. The source of the data was obtained based on the results of recommendations through interviews with BK teachers. The results showed that 2 AKL Class XII students at Mahardika Batujajar Vocational School had low self-efficacy in facing the Expertise Competency Test (UKK) during the covid-19 pandemic, which were generally less confident in their abilities, less able to manage situations, not confident, fear, lack of self-awareness, anxiety, and doubt in making structured plans.Keywords: Self-Efficacy, Pandemic Covid-19